Sock Hops and Red Rooms: On Teaching Jane Eyre to Marginalized Students - Elsherief, Heba (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2020)
This short story illustrates an occasion of culturally responsive and sustaining pedagogical practices in relation to the canonical texts which are often used in urban classrooms. In it, a lesson on Jane Eyre’s childhood point of view and mode of introspectiveness delves into a tale of dancing and Otherness. The story shows that in spaces where the majority of students are marginalized, opportunities wherein diverse bodies are encouraged to respond in ways that are meaningful to them, to “write themselves” into narratives, are crucial for inclusive and equity-building engagement.